The Role of Fibrinolytic Activity of Blood Plasma in the Development of Obstetric Complications in Overweight Pregnant Women with Metabolic Dysfunction-Associated Steatohepatitis: A Prospective Cohort Study - Lina Bahniy; Svitlana Heryak; Nataliya Bahniy; Viktoriia Kuchmii (IMR Press, 2024)
Background: Obesity and hyperlipidaemia during pregnancy increase the risk of metabolic dysfunction-associated steatotic liver disease. Our aim was to evaluate changes in the fibrinolytic system in overweight pregnant women due to metabolic dysfunction-associated steatohepatitis, compared with a control group and its impact on the development of gestational complications. Methods: Prospective cohort study included 69 overweight pregnant women with metabolic dysfunction-associated steatohepatitis and 30 healthy pregnant women (control group). All pregnants with metabolic dysfunction-associated steatohepatitis and obesity were divided into 3 subgroups: IA - 23 overweight pregnant women, IB - 25 pregnants with obesity grade 1, IC - 24 pregnant women with obesity grade 2. To evaluate the fibrinolysis system, we studied total, enzymatic and non-enzymatic fibrinolytic activity of plasma. Results: The total fibrinolytic activity of IA, IB and IC groups were, respectively, 15%, 19% and 23% lower than that of controls and the enzymatic fibrinolytic activity in overweight pregnant women with metabolic dysfunction-associated steatohepatitis of IA, IB and IC groups were, respectively 28%, 43% and 54% lower than in controls. Marked suppression of the total fibrinolytic activity and enzymatic fibrinolytic activity of the blood plasma was established in overweight pregnant women with metabolic dysfunction-associated steatohepatitis. These changes can serve as a prerequisite for the occurrence of microthrombosis with the subsequent development of placental dysfunction, fetal growth restriction and fetal distress. Conclusions: There are disorders in the system of the coagulation function with a tendency to peripheral microthrombosis, disseminated intravascular coagulation syndrome and macrothrombosis, which can be early prognostic criteria in the development of obstetric and perinatal complications in overweight pregnant women with metabolic dysfunction-associated steatohepatitis. Clinical Trial Registration: This work is a fragment of the complex research work of the Department of Obstetrics and Gynecology of I. Horbachevsky Ternopil National Medical University of the Ministry of Health of Ukraine "A comprehensive approach to symptom control, recurrent and long-term prognosis in conditions of comorbid pathology in internal medicine clinic and family doctor's practice" (state registration number 0223U000022, 0118U000361 https://nrat.ukrintei.ua/en/searchdoc/).